Contents of Western Sociology of Religion as a Science and Educational Discipline - Fylypovyč, Ljudmyla Oleksandrivna (Ukrai͏̈ns'ke relihijeznavstvo, 2003)
Sociology of religion in the West is a field of knowledge with at least 100 years of history. As a science and as a discipline, the sociology of religion has been developing in most Western universities since the late nineteenth century, having established traditions, forming well-known schools, areas related to the names of famous scholars. The total number of researchers of religion abroad has never been counted, but there are more than a thousand different centers, universities, colleges where religion is taught and studied. If we assume that each of them has an average of 10 religious scholars, theologians, then the army of scholars of religion is amazing. Most of them are united in representative associations of researchers of religion, which have a clear sociological color. Among them are the most famous International Society for the Sociology of Religion (ISSR) and the Society for Scientific Study of Religion (SSSR).